Editorial Information - Editors, PJLS (Polskie Studia Krajobrazowe, 2019)
Editor of the Volume: Monika Stobiecka Articles by J. Schollenberger, P. Szczepański and J. Zimpel translated by Delfina Potocka Proof reading: Kamil Lemanek Graphic Design: Ewa Mikuła, Katarzyna Turkowska Typesetting: Monika Rawska / Legut